Oči in slepe pege časa - Senegačnik, Brane (Keria (Ljubljana), 2011)
Aeschylus' Persians has caused many quandaries and divergences in interpretation, both in terms of its exceptional (historical) subject-matter and of the author's true purpose, that is, the function of the play. While reading works of antiquity through the cultural lens of our own age is unavoidable and may prove fruitful, it can only carry weight if it takes into account a basic hermeneutic principle, that is, if it includes a reflection on the interpreter's own starting-points, shedding light on their relativity. The oldest preserved work of European drama is generally interpreted within cultural and political horizons as defined by modern epistemic concepts, while its religious dimension passes unnoticed, although it should not be neglected - not only because of the general cultic framework which determined the original "hermeneutics" of tragedies, but also because of the text itself. This conceptually conditioned neglect of the "non-negligible" is described by the author as a "blind spot of time" and associated with changes to the anthropological horizon. Moreover, springing from a shift in self-understanding, and consequently in understanding history and culture, rather than from an inherent logic of science, these changes are largely perceived as an expression of the prevailing zeitgeist. A different reading is suggested - one based on a religious interpretive horizon, where clarifications and interpretive shifts, sprung from a different understanding of the social and cultural context, may significantly affect the perception of the work as a whole, without reducing it to what is meaningful solely within a delimited culturological and sociological horizon. After surveying the traditional dilemmas of literary history (the framework of tetralogy, dramaturgical structure, critical opinions on the effectiveness and artistic merit of the play), the paper addresses the Persians' association with, or even dependence on, factual history: the events portrayed (at times with obvious historical inaccuracy) and the cultural mentality of the original audience. In this context, the dream of Queen Atossa (176-199) is addressed as well, with an emphasis on the non-nationalist message at the core of the dream vision. Particular attention is paid to the symbolic dimension of clothing: as symbols, garments mark a secondary, non-basic feature, which is not the same as the (unnamed) primary, physical feature. In the symbolic economy of the Persians, the very garments and gear are connected to the central idea - the destructiveness of man's hybris -, graphically illustrating the transience of all things human.
Keywords: Aeschylus; Aeschylus: Peržani; grška dramatika; grška tragedija; literarne študije; Persae; starogrška književnost